(untitled) - Reinhold Görling; Christian Gudehus; Andreas Hamburger; Gabriele Schwab; Jürgen Straub; Annette Streeck-Fischer; Wolfgang Wöller (Trauma Kultur Gesellschaft, 2023)
Trauma Culture Society is an interdisciplinary journal of psychotraumatology. It is edited by closely cooperating experts from medicine, psychology and psychoanalysis, social and cultural sciences, and philosophy. In a broad spectrum of topics, it always deals with severe psychological injuries from which people suffer in the long term, often for life. Not only are individual fates illuminated and the experience of the wounded examined, but medical, psychodynamic, and therapeutic treatment options are also discussed, and the social significance of and cultural approaches to trauma are explored. Excessive violence, its manifold preconditions as well as its subjective and social, also intergenerationally inherited consequences have shaped human coexistence since time immemorial. Traumas are part of the lives of many people - also in our present, worldwide. The new journal is dedicated to this complex issue. It combines psychotraumatological perspectives with the analysis of social, historical and cultural forms of life, in which very different ways of dealing with psychological injuries and their social consequences can be observed - from denial, trivialization or repression to conscious enlightenment in political cultures of remembrance, which commemorate the victims of excessive violence as well as the transgenerational transmission of their suffering even after decades and centuries. This can take many forms and media. The booklets contain original works, workshop reports from current research projects, practice reports, book and film reviews, and clinical case presentations.